Integration of water collection and purification on cactus- and beetle-inspired eco-friendly superwettable materials. (1st November 2021) - Zhu, Hai; Cai, Si; Zhou, Jia; Li, Siqi; Wang, Dawei; Zhu, Juan; Wu, Yaqin; Huang, Yu; Yuan, Songhu; Jin, Shiwei; Xia, Fan
Highlights: The low-cost and environmentally friendly superwetting surfaces were fabricated inspired by cactus spines and desert beetles. The wedge-shaped superhydrophilic patterns generated self-driven water transportation for enhancement of water collection. The system combining water collection and purification ensured safe and available freshwater from atmosphere. Ten zebrafishes kept alive in collected and purified water even for over 480 h. Abstract: Freshwater shortage has been a terrible threat for the sustainable progress and development of human society in 21st century. Inspired from natural creatures, harvesting water from atmosphere has been a feasible and effective method to alleviate water shortage crisis. However, the recent works related to water collection just focuses on how to optimize fog-harvesting manners and efficiencies, the safety and availability of collected water are always ignored. In this paper, we proposed a new strategy accessed to freshwater resources through combining water collection and purification together on eco-friendly superwettable material inspired by cactus spines and desert beetles. Six superhydrophilic wedge-shaped patterns prepared by P25 TiO2 nanoparticles (NPs) were constructed on candle soot@polydimethylsiloxane (CS@PDMS) superhydrophobic coating. The special superhydrophilic regions not only effectively captured water from foggy environment but generated Laplace pressure gradient to faster drive water away. The bioinspired material exhibited an efficient water collection rate (WCR) of 14.9 ± 0.2 mg min −1 cm −2, which was 5.3 and 2.5 times larger than that on uniformed superhydrophilic and superhydrophobic surfaces, respectively. Because of the existence of photocatalytic P25 NPs in wetting areas, the harvested wastewater containing nine kinds of pesticides (0.5 mg/L) could be purified in low concentrations (< 5%) under UV light (365 nm, 5.0 ± 0.6 mW cm −2 ). Ten zebrafishes were still alive in such purified water for 72 h, as a contrast, the same number of fishes would almost die in untreated harvested wastewater in just 7 h. This work indeed opens up a new sight to freshwater accessibility, aiming to a promising project for alleviating water shortage around the world. Graphical abstract: Inspired by cactus spines and desert beetles, an integrated system for both water collection and purification on superwettable material was developed Image, graphical abstract .